Loss of exosomal micro-RNA-200b-3p from hypoxia cancer-associated fibroblasts reduces sensitivity to 5-flourouracil in colorectal cancer through targeting high-mobility group box 3 - Yuan, Hang; Chen, Bingchen; Chai, Rui; Gong, Wenjing; Wan, Ziang; Zheng, Boan; Hu, Xinye; Guo, Yang; Gao, Shan; Dai, Qiaoqiong; Yu, Peng; Tu, Shiliang (Frontiers in Oncology, 2022)
Background: Hypoxia-mediated progression of tumor progression is a major problem in Hypoxia-mediated tumor progression is a major problem in colorectal cancer (CRC). MicroRNA (miR)-200b-3p can attenuate the tumorigenesis in CRC, while exosomal miRNAs derived from cancer-associated fibroblasts (CAFs) can promote cancer progression. Nevertheless, the function of exosomal miR-200b-3p derived from CAFs in CRC remains unclear. In this study, CAFs and normal fibroblasts (NFs) were isolated from CRC and adjacent normal tissues. Next, exosomes were isolated from the supernatants of CAFs cultured under normoxia and hypoxia. Cell viability was tested using the cell counting kit-8 assay, and flow cytometry was used to assess cell apoptosis. Cell invasion and migration were evaluated using the transwell assay. Dual-luciferase was used to investigate the relationship between miR-200b-3p and high mobility group box 3 (HMBG3). Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was performed to determine the miR-200b-3p and HMBG3 level. Our results found that miR-200b-3p level was sharply reduced in CRC tissues compared to adjacent normal tissues. Additionally, miR-200b-3p level was declined in exosomes derived from hypoxic CAFs compared to exosomes derived from CAFs under normoxia. Exosomes derived from hypoxic CAFs weakened the sensitivity of CRC cells to 5-Fluorouracil (5-FU) compared to hypoxic CAFs-derived exosomes. However, hypoxic CAFs-derived exosomes with upregulated miR-200b-3p increased the sensitivity of CRC cells to 5-Fluorouracil (5-FU) compared to hypoxic CAFs-derived exosomes. In addition, HMBG3 was identified as the downstream target of miR-200b-3p in CRC cells, and its overexpression partially reversed the anti-tumor effect of the miR-200b-3p agomir on CRC via mediation of the β-catenin/c-Myc axis. Furthermore, compared to exosomes derived from normoxia CAFs, exosomes derived from hypoxic CAFs weakened the therapeutic effects of 5-FU on CRC in vivo via the upregulation of HMGB3 levels. Collectively, loss of exosomal miR-200b-3p in hypoxia CAFs reduced the sensitivity to 5-FU in CRC by targeting HMGB3. Thus, our research outlines a novel method for the treatment of CRC.